Predecessors' attitude toward conflict predictor of family business sustainability - Salim, Linda; Mohd Shariff, Mohd Noor; Ahmad Arshad, Darwina; Surya Saputra, Ruswiati (2016)
Using qualitative interviews to understand the mindset of family business leaders in succession, this study proposes that attitude toward conflict is an important decision making element.Collective case studies uncover how attitude toward conflict predicts decision making during succession and influences optimism on the future of the firms. Findings of the study suggest that predecessors who welcome conflicts as part of family firms take a more relaxed attitude toward succession, with a wider next generation talent pool.This group is also more egalitarian in strategic decision making and optimistic toward the future of the firms. Predecessors who avoid conflict have smaller talent pool, making decisions to nominate select few for the position.They are cautious, making decisions for the successors, and are pessimistic about the future of the firms.Contributions from this study are threefold.First, we introduce the use of attitude toward conflict to measure predecessor's behavior during succession.Second, through identification of attitude toward conflict, we contribute to the literature by predicting predecessor's optimism toward the future of the firms in the hands of the next generation.Third, this study contributes another dimension to reciprocal nepotism through discovery that family business upholding reciprocal nepotism behave differently.